Implementation of Anti-Corruption Villages Based on Local Wisdom: A Study in Banyubiru Village, Semarang Regency - Slamet Sugi Rahayu; Andi Suhardiyanto (Universitas Negeri Semarang, 2026)
The increasing prevalence of corruption poses a serious challenge, as the increasing authority and allocation of village funds have not been fully balanced by accountable governance. The Anti-Corruption Village Program, initiated by the Corruption Eradication Commission (KPK), is a corruption prevention effort based on strengthening governance and community participation. This study aims to analyze the implementation of the Anti-Corruption Village Program based on local wisdom in Banyubiru Village, Semarang Regency, and examine the role of community awareness and the division of functions between the village government and traditional institutions in supporting the program's success. The study used a qualitative approach with a case study method. Data were collected through interviews, observation, and documentation involving the village head, village secretary, village officials, traditional institutions, the Village Consultative Body, and community representatives. The results show that the Anti-Corruption Village Program in Banyubiru Village was implemented effectively because it was integrated with local wisdom values such as prasaja, honesty, mutual cooperation, and deliberation. Collective community awareness serves as social capital that encourages active participation in planning, program management, and village budget oversight. Village governments provide a space for community aspirations and trust in budget management, while carrying out control, monitoring, and evaluation functions transparently. This study recommends strengthening the integration of local wisdom as a sustainable strategy for preventing corruption at the village level.